Pedagogical Advisors and EFL Teachers’ scaffolding in post-observation Feedback conferences in Benin - Hounhanou, Arlette Joséline Viviane (My University, 2019)
Lev Vygotsky view of development focuses heavily on language and interaction, and the role they play in helping learners acquire an understanding of the culture in which they live. In the same way that teachers are encouraged to engage students in meaningful learning tasks, pedagogical advisors provide assistance for EFL teachers so that they gain from instructional scaffolding in the form of modeling, questions, prompts, and cues. This paper explores how Pedagogical advisors provide guidance for EFL teachers especially during the post observation feedback sessions. A total of thirty three trainees teachers from the training college (ENS) and seven pedagogical advisors (PA) took part in this research. Overall, the results indicated that a great majority of participants really felt uncomfortable regarding the assistance they received from their mentors and PA after observation. Some of them have a positive view about post observation feedbacks. The outcomes of this research invite PA to focus more on the convention of feedback, and mentors to include the social, and linguistic aspects at the heart of scaffolding.
Keywords: Pedagogical Advisors; trainees teachers; scaffolding; observation; feedbac